Fall of the Berlin Wall: Reflection of the Historical Event in the Newest German Drama - Rafizovna Lisenko, Anzhela (2021)
In this article, the authors refer to the play “Kein Schiff wird kommen” (“No ship will come”), 2010, by a young German playwright Nisa-Momme Stockmann, in which “historical events are refracted in the context of personal events of the characters”. In the center of the play is a young man, a writer, who was commissioned by the theater to write about the fall of the Berlin Wall. The protagonist of the play is a representative of an indifferent generation, far from politics and history. In 1989, he himself was a child, and the reunification of Germany, at first glance, had no effect on him. However, upon closer inspection, it turns out that the fall of the wall turned out to be an important event for him and his family. Only an appeal to the history of the country and the family helps the character to resolve the internal conflict. This shows the relationship with the tradition of German literature after World War II: German writers often refer to historical facts in their works. The key topic is of guilt and responsibility, which has been rethought in the literature over the past 60 years. Analysing the drama allows us to conclude that modern young people reject their past, which causes the character's personality crisis, and it also leads to failure in communication. In addition, alongside with ousting the past, the problem of German identity arises.